The Effect of Lavender Aromatherapy on Reducing Anxiety in Primigravida Mothers during Kala I Latent Phase: A Pra-experimental Study - Vivi Dwi Putri; Popy Apriyanti; Apriyanti Aini (Lentera Perawat, 2025)
Anxiety is a mixture of several unpleasant emotions and is dominated by uncontrollable fear of conditions that threaten their condition and lead to things that are not necessarily happening. This anxiety includes emotional, cognitive and psychological in general anxiety can be influenced by several symptoms that are similar to people who experience depression. Each essential oil has a unique pharmacological effect such as antibacterial, antiviral, diuretic, vasodilator and stimulates adrenaline. This study aims to evaluate the effectiveness of lavender aromatherapy on reducing anxiety levels in primigravida mothers in the first stage of latent phase at independent midwife practice Nikma Tunnisak in 2024. The research method used was a pra-experimental with a population of all mothers in labor with anxiety at PMB Nikma Tunnisak with a sample size of 13 respondents. The research instrument used a questionnaire. From the results of the study with the results of the paired T-test, namely (p - value = 0.000) it can be concluded that there is a significant effect that the administration of lavender aromatherapy is effective in overcoming the anxiety levels of primigravida mothers in the first stage of latent phase. It is hoped that the provision of lavender aromatherapy can be implemented comprehensively in Indonesian health services.